The Use of Metalanguage Among Second Language Learners to Mediate L2 Grammar Learning - Harun, Haliza; Abdullah, Norhana; Ab Wahab, Nur Syuhada; Zainuddin, Nurkhamimi (Universiti Utara Malaysia Press, 2017)
Purpose - This study investigated the use of metalanguage as a mediational tool in understanding targeted grammatical concepts from the perspective of the Sociocultural approach (SCT) in learning a second language (L2).